Perancangan Sofa Ergonomis untuk Café di Surabaya - Alfin Septariano Louis; Grace Mulyono (Intra, 2018)
In this era of globalization, people of Surabaya tend to frequently visit cafés, especially because there are lots of cafes in Surabaya with various design concepts. People will choose café that is comfortable and has great atmosphere. Based on those comfort places, some of their furnitures, especially sofas, may neither be comfortable nor ergonomic. Sometimes the sofa’s fabric and leather materials are not comfortable enough, have broken sponges, and damaged construction.The suitable method for the design of this sofa based on the problems is conducted with the questionnaire data about the comfortability of the sofa for visitors - café visitors and data collection - the data includes sofas in some cafes around Surabaya. By knowing the problems and data, designer will be able to know which are the best materials for the construction, and most comfortable for users.The concept used for this sofa design is universal concept, which is comfortable and ergonomic in terms of size, material, and comfort aspect. The modular design of the sofa equipped with charging facility to accommodate users’ needs, the needs of interior elements and space for ads, designed in a unique form using hollow iron material so this sofa can be used for a long-time period, and the design will be everlasting.